2005
DOI: 10.1136/gut.2004.040360
|View full text |Cite
|
Sign up to set email alerts
|

Patients with active inflammatory bowel disease lack immature peripheral blood plasmacytoid and myeloid dendritic cells

Abstract: Background: Breakdown of tolerance against the commensal microflora is believed to be a major factor in the pathogenesis of inflammatory bowel disease (IBD). Dendritic cells (DC) have been implicated in this process in various animal models, but data on human DC in IBD are very limited. Aim: To characterise plasmacytoid DC (PDC) and myeloid DC (MDC) in patients with active versus inactive IBD and healthy controls. Patients and Methods: Peripheral blood was obtained from 106 patients (Crohn's disease (CD) n = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 58 publications
10
100
0
1
Order By: Relevance
“…The lower constitutive expression of the costimulatory molecules CD80, CD86, and CD40 on pDCs than mDCs clearly documented with our assay is in accordance with the tolerogenic function ascribed to pDCs (16). A few observations of lower expression of these markers on pDCs have been previously reported, but with methods that used isolated or cultured PBDCs, or compared data obtained from different tubes (17)(18)(19)(20). In this respect, the direct comparison between DC subsets made possible by our 6-color assay may be more reliable.…”
Section: Discussionsupporting
confidence: 66%
“…The lower constitutive expression of the costimulatory molecules CD80, CD86, and CD40 on pDCs than mDCs clearly documented with our assay is in accordance with the tolerogenic function ascribed to pDCs (16). A few observations of lower expression of these markers on pDCs have been previously reported, but with methods that used isolated or cultured PBDCs, or compared data obtained from different tubes (17)(18)(19)(20). In this respect, the direct comparison between DC subsets made possible by our 6-color assay may be more reliable.…”
Section: Discussionsupporting
confidence: 66%
“…[26][27][28] On the other hand, previous studies have shown the lack of peripheral blood pDCs in patients with active IBD, and instead their accumulation in the inflamed colonic mucosa and mesenteric lymph node (MLN) and dysfunction. 29,30 However, how pDCs contribute to the development of IBD remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The current discourse in this context refers to an imbalance between tolerance to commensal microbiota or food-derived antigens and immune responses to pathogens [1]. Thus, mucosal inflammation observed in CrD is triggered by such dysregulation of the innate as well as adaptive immune responses [1,75]. A molecule like GP2 interacting with FimH positive microbes and facilitating the phagocytosis thereof could play a major role in triggering and perpetuating inflammatory processes in CrD.…”
Section: Autoimmunity To Glycoprotein 2 In the Pathophysiology Of Cromentioning
confidence: 99%